Intrathecally Administered Apelin-13 Alleviated Complete Freund’s Adjuvant-Induced Inflammatory Pain in Mice - Lv, Shuangyu; Zhang, Xiaomei; Zhou, Yuchen; Feng, Yu; Yang, Yanjie; Wang, Xinchun (Frontiers in Pharmacology, 2020)
Apelin is the endogenous ligand for APJ, a G-protein-coupled receptor. Apelin gene and protein are widely distributed in the central nervous system and peripheral tissue. Our previous study showed that apelin-13 induced an antinociceptive effect in acute pain using a visceral pain model and tail-flick test. However, the role of apelin in chronic inflammatory pain is still unclear. We used a mouse model of complete Freund’s adjuvant (CFA)-induced inflammatory pain. After intrathecal (i.t.) injection of apelin-13 (0.1, 1, and 10 nmol/mouse), paw withdrawal latency in response to thermal stimulation and paw withdrawal threshold in response to Von Frey ﬁlament stimulation were recorded. mRNA and protein expression, concentration of glutamic acid (Glu), and number of c-Fos-positive cells in lumbar spinal cord (L4/5) were determined. Our results demonstrated that Apln gene expression in the lumbar spinal cord was down-regulated in the CFA pain model, compared with vehicle control. I.t. injection of apelin-13 (10 nmol/mouse) alleviated CFA-induced inflammatory pain. In addition, apelin-13 induced a more potent antinociceptive effect than did apelin-36 and (pyr)apelin-13. The analgesic activity of apelin-13 could be blocked by APJ antagonist apelin-13(F13A). I.t. apelin-13 attenuated the increased expression of Aplnr, Grin2b, Camk2d and c-Fos genes caused by CFA in the mouse lumbar spinal cord. The elevated Glu concentration and NMDA receptor 2B (also known as GluN2B) expression in lumbar spinal cord were mitigated by apelin-13. Apelin-13 significantly reduced the number of Fos-positive cells in laminae III and IV/V of the dorsal horn. This study indicated that i.t. apelin-13 exerted an analgesic effect on the inflammatory pain induced by CFA. The effect was mediated by activation of APJ, and inhibition of Glu/GluN2B function and neural activity of the spinal dorsal horn.